MARKETING MIX MODEL ISLAMIC VALUES AS A MARKETING STRATEGY AT MAN 1 MUSI BANYUASIN - Adhelmi, Adhelmi; Yuniar, Yuniar; Astuti, Mardiah; Rahmawati, Destiani (Jurnal Asy-Syukriyyah, 2025)
This study analyzes the implementation of the Mix Marketing Model as a marketing strategy at MAN 1 Musi Banyuasin to increase the interest of prospective students. Using a qualitative method with a descriptive approach and case studies, the study was conducted for 6 months (August 2024-January 2025) with data collection through in-depth interviews, observations, and documentation. The results of the study indicate that the implementation of the Mix Marketing Model with a focus on developing diverse, quality, and unique educational products has succeeded in significantly increasing the number of registrants from 182 (2021/2022) to 520 (2024/2025). Leading programs such as the humanist madrasah velue, PPDB roadshow, Mansamuba Festival, and 24 extracurricular activities are the main differentiations of the madrasah. A comprehensive approach involving all stakeholders and continuous evaluation produces educational products that are in accordance with the needs and expectations of users. The implementation of the Mix Marketing Model has proven effective in building a positive image and increasing the competitiveness of madrasahs in the era of globalization. madrasah effectively aligns its offerings with the needs of the local community while integrating Islamic values.